PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN QUIZIZZ TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Evi latifah; Rasmitadila; Irwan Efendi (AL - KAFF: JURNAL SOSIAL HUMANIORA, 2022)
The interesting use of learning media, can increase the motivation to learn learners, get bored, and spirit in following learning, Media learning as a tool to encourage learners to achieve their competence, in addition can motivate the learners in the learning. For that, educators have a role in using media learning, especially technological media. The purpose of this research is to test, the influence of significant media learning Quizizz to the motivation to learn learners of class VI elementary School of Islam integrated Al-Fatih District Cigombong Bogor Regency. The research technique used is a descriptive quantitative with research design i.e. functional correlation. The research Data was collected using questionnaire poll techniques, with the number of respondents all students of class VI SDIT Al-Fatih as many as 42 students. The results of research analysis showed that there is a significant influence between the use of media learning quizizz to the motivation to learn learners know the value of Thitung 4.854 > 2.021 This or the value of Thitung greater than with the error level is 5% with a significant yield of 0.000 < 0.05 so that H0 rejected and Ha accepted, the magnitude of the influence is 37.1%, while the influence from the outside is not in the study of 62.9%. So the conclusion of this research is that there is a significant influence of the use of media learning quizizz towards the motivation of learning learners.